2019
DOI: 10.1155/2019/6542410
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Applicability of Random Forest, Stochastic Gradient Boosted Model, and Extreme Learning Machine Methods to the Quantitative Precipitation Estimation of the Radar Data: A Case Study to Gwangdeoksan Radar, South Korea, in 2018

Abstract: Machine learning algorithms should be tested for use in quantitative precipitation estimation models of rain radar data in South Korea because such an application can provide a more accurate estimate of rainfall than the conventional ZR relationship-based model. The applicability of random forest, stochastic gradient boosted model, and extreme learning machine methods to quantitative precipitation estimation models was investigated using case studies with polarization radar data from Gwangdeoksan radar station… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 47 publications
(47 reference statements)
0
6
1
Order By: Relevance
“…Nevertheless, the monthly mean visibility estimation accuracy was as follows: bias=-0.11 km, RMSE=2.05 km, and r=0.93. These results showed lower variability and higher accuracy than previous studies that quantitatively estimated precipitation using satellite-based (Nguyen et al, 2021), radar-based (Shin et al, 2019), andnumerical model-based (Ko et al, 2020) data using ML algorithms. Therefore, the application of…”
Section: Accepted Manuscriptcontrasting
confidence: 54%
“…Nevertheless, the monthly mean visibility estimation accuracy was as follows: bias=-0.11 km, RMSE=2.05 km, and r=0.93. These results showed lower variability and higher accuracy than previous studies that quantitatively estimated precipitation using satellite-based (Nguyen et al, 2021), radar-based (Shin et al, 2019), andnumerical model-based (Ko et al, 2020) data using ML algorithms. Therefore, the application of…”
Section: Accepted Manuscriptcontrasting
confidence: 54%
“…Therefore, the deep neural network is a new option for improving the accuracy of QPE (Wu et al, 2021). Shin et al (2019) evaluated the applicability of random forests, stochastic gradient augmentation models, and extreme learning machine methods to QPE and used multivariate combinations as inputs. The results show that the approach based on machine learning performs better than the model with Z-R relationship and resolves the time lag between the radar data and ground observations, and the accuracy is improved by an appropriate combination of multiple input variables.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the introduction of remote observation instruments, such as radar and satellites, generating quantitative rainfall data remains challenging because of uncertainty arising from the di culties in observations over mountains and oceans (Tesfagiorgis et Studies have attempted to merge radar and ground observations or use machine learning to generate quantitative rainfall data (Tang et al 2018;Shin et al 2019;Ro and Yoo 2020). These research showed that how important to secure accurate ground observation data for precise analysis of water resources and water cycle.…”
Section: )mentioning
confidence: 99%